(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2016)
Currently, tariffs do not represent the main barrier to foreign trade, due to the continued reduction of these measures in the multilateral or bilateral level. In contrast, non-tariff measures have increased to be considered as the main concern for exports. In this context, one kind of such measures becomes more important, the sanitary and phytosanitary (SPS) measures. SPS measures serve to protect the health of people, animals and plants against risks associated with diseases, pests between others; however, by the design of those measures, they can distort trade or even been used for protectionist purposes in favor of national industries of importing countries. This article questions whether Peru has achieved real market access for its agricultural and fishery products, because of the wide range of international trade agreements in force. In this sense, historical and pending cases are presented in terms of market access due to SPS measures, like the access for Peruvian avocadoes In the Japanese market. Furthermore, the provisions of trade agreements in terms of sanitary and phytosanitary measures are analyzed in order to present potential opportunities that are established in these agreements and how they encourage trade. It is also presented that those kind of measures have not been used to facilitate Peruvian foreign trade.